Visfatin serum level and expression in subcutaneous and visceral adipose tissue in prepubertal boys. Issue 5 (21st October 2015) - Novak, S.; Divkovic, D.; Drenjancevic, I.; Cosic, A.; Selthofer‐Relatic, K.
Summary: Background: The biological role of visfatin in humans, especially in eutrophic and healthy children, is not understood yet, except for its link to obesity‐related disorders in adolescents and adults. Objectives: To determine the physiological values of serum visfatin concentrations, and visfatin mRNA expression in subcutaneous (SAT) and visceral adipose tissue (VAT), and to correlate them with anthropometric/metabolic data in prepubertal healthy boys. Methods: The study included 59 healthy boys, age 1–10 years, hospitalized for elective surgery, divided according to age into group I (1–3 years old), group II (3–7 years old) and group III (7–10 years old). Anthropometric and biochemical measurements, and the visfatin serum and mRNA level in SAT and VAT were determined in all patients. Results: Visfatin mRNA expression was higher in SAT compared with VAT in all three studied groups. Highest visfatin mRNA was found in SAT of group III compared with group II ( P = 0.030). VAT visfatin mRNA expression negatively correlates with body weight ( P = 0.039), waist circumference ( P = 0.027) and morning glucose level ( P = 0.007). Conclusion: Lack of changes in serum visfatin level despite the changes in visfatin mRNA expression of adipose tissue suggests paracrine effect of visfatin rather than endocrine. Negative correlation of visfatin VAT mRNA expression with anthropometric parameters indicates important role of VAT visfatin in maturation and in glucose metabolism.